2018
DOI: 10.1002/bio.3479
|View full text |Cite
|
Sign up to set email alerts
|

Factorial design optimization of micelle enhanced synchronous spectrofluorimetric assay of Omarigliptin: Applied to content uniformity testing and in vitro drug release

Abstract: A micelle enhanced spectrofluorimetric method was developed for determination of Omarigliptin (OMG) based on its native fluorescence behavior. The interaction of OMG with surfactants and macromolecules was studied. In aqueous solution, the relative fluorescence intensity (RFI) of OMG was enhanced by 24% in the presence of Tween 80 at pH 3.5. The optimal conditions for the micelle enhanced fluorescence were attained by Minitab® program using Plackett-Burman factorial design. Pareto chart, contour plots and surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…48 Another reason is the tendency of CS to hydrate, limitedly swell when it comes in contact with high-pH dissolution media of a high pH, then form a gelatinous mass that slows drug diffusion. 49,50 F3 also showed sustained release due to the formation of a three-dimensional physical network of rigid gel.…”
Section: Discussionmentioning
confidence: 99%
“…48 Another reason is the tendency of CS to hydrate, limitedly swell when it comes in contact with high-pH dissolution media of a high pH, then form a gelatinous mass that slows drug diffusion. 49,50 F3 also showed sustained release due to the formation of a three-dimensional physical network of rigid gel.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review showed that few reported methods were available for determination of OMG either alone or in combination with other drugs. These methods comprise HPLC [ 8 10 ], spectrofluorimetry [ 11 ], spectrophotometry [ 12 ], and LC-MS/MS [ 13 ]. Concerning MET, a number of reported methods was available including HPLC [ 14 20 ], spectrophotometry [ 21 24 ], spectrofluorimetry [ 25 , 26 ], LC-MS/MS [ 27 30 ], and TLC [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Omarigliptin (OMR) is chemically known as [17]. It is a recent antidiabetic drug used for treatment of type II diabetes mellitus [18].…”
Section: Introductionmentioning
confidence: 99%
“…Being recently developed drug, OMR has not yet been listed in any pharmacopeia [22][23][24]. Literature survey revealed that different analytical techniques have been developed for OMR determination such as spectrofluorometry [17] and chromatography [19,[25][26][27]. Moreover, our previously reported stability study revealed that the drug was susceptible to hydrolytic and oxidative degradations [27].…”
Section: Introductionmentioning
confidence: 99%